FUNCTIONAL, SEMANTIC, AND COGNITIVE DESCRIPTION OF THE CATEGORY OF HABITUALITY IN ENGLISH AND UZBEK - Dilnoza Oblokulova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article explores the category of habituality in English and Uzbek from functional, semantic, and cognitive perspectives. Habituality is understood as a linguistic means of expressing regularly repeated actions or states that are characteristic of a subject over a period of time. The study analyzes how habitual meaning is encoded in both languages, focusing on grammatical structures, contextual markers, and cognitive interpretation. A comparative approach reveals that while English relies on syntactic constructions and contextual cues, Uzbek expresses habituality through morphological means and aspectual nuances. The research also highlights the cognitive basis of habituality as a reflection of human experience and routine behavior.